PENGARUH CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP PEMAHAMAN MEMBACA SISWA - Anni Holila Pulungan (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2012)
The study deals with the Contextual Teaching and Learning of the students’ reading comprehension at junior high school. Contextual Teaching and Learning is a new alternative for every teachers to relate the materials to the real world. The aims of the research are to analyze the effect of non and CTL method of the students’ reading comprehension.  The research method is an experimental method. The data analysis is taken from the two classess. Then, they divided into two  groups, the control and experimental group. The major findings of the study shows that the effect of Contextual Teaching and Learning on the students’ reading comprehension is better than the non CTL method-lecture method for the junior high school students.